Perilaku Konsumen Muslim di Lombok Berdasarkan Religiusitas dan Gaya Hidup - Umu Rosyidah; Puji Handayati (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This paper is the result of research that aims to identify and analyze whether religiosity and lifestyle partially or simultaneously contribute to the influence of Muslim consumer attitudes in Lombok. The research results were processed by SPSS 20.0 testing. and the results both partially and simultaneously affect the behavior of Muslim consumers. And of the two variables, the more significant contribution to Muslim consumer behavior is the religiosity factor. It was found that at the level of religiosity most of the respondents stated their agreement on the elements that make up the dimensions of aqidah, shari'ah, religious knowledge, appreciation, and practice dimensions. This means that the consumer's decision to buy a product is in accordance with the content of their faith. Religious activities do not only occur when a person carries out rituals, but also when carrying out other activities such as buying and selling methods, consuming etc. For lifestyle variables, 78% of respondents reported their agreement on the main factors that make lifestyles, namely demographic factors such as education, age and total income that affect a person's lifestyle. Meanwhile, on psychographic factors, 91% of respondents agreed that psychographic factors such as interests, interests, hobbies and opinions affect a person's lifestyle. In this study, the determining variables in consumption activities are the consumption foundation and the consumption principle.